La política fiscal municipal frente a la crisis: miradas desde la prensa local (Posadas, territorio de Misiones, 1914-1918) - Luz Irene Pyke (Nuevo mundo - Mundos Nuevos, 2023)
The paper approaches ways in which the debates around the tax reform in Argentina were reflected and readjusted into municipal levels during the WWI economic crisis. By taking the case of Posadas, capital city of the national territory of Misiones, it proposes to observe how the new debates on the tax system and the municipal attributions to establish a more progressive levy were reflected from the local newspaper La Tarde. Through this analyses it is sustained that the issues discussed show the circulation of ideas according to which municipalities were conceived as government institutions provided with the necessary attributions to introduce tax reforms or redirect their tax policies based on a progressive levy, and also regulate the prices of basic foodstuffs, in order to favor low-income sectors affected by the crisis. Likewise, we argue that although these conceptions were nurtured by widespread economic ideas such as Georgism, they also received influence from the experiences of other municipalities that worked as models of what could be done. In this context, municipal initiatives can be understood as inserted in a wider field of discussions over the scope of municipal capacities during the crisis and not only as local responses.